Membangun Sistem Informasi Apotek sebagai Media Pelayanan di Masa Pandemi Corona Virus Disease 19 (Covid-19) - Aprilia Manganti (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2021)
Currently, technology is developing rapidly in various aspects that are well integrated, such as the Sendang Farma Pharmacy. The system used is still considered too complicated so that the admin is less painstaking in data entry and website usage. This results in the number of goods in the system and actual stocks that do not match so that consumers are disappointed because the drug supply is not available. The scope of the problem currently observed is how to design information systems at pharmacies that aim to facilitate data processing in information so that it is effective and efficient according to user desires. The design of this system is also useful for improving customer service during the Covid-19 pandemic so that it can increase customer satisfaction. The method used in this research is the SDLC (System Development Life Cycle) method with the waterfall model. The website of the Sendang Farma Pharmacy is designed using a programming language, MySQL as a database and PHP. The result of this system is a pharmacy information system that will get information and drug inventory at the Sendang Farma Pharmacy.